THE EFFECT OF RED SESBANIA (SESBANIA GRANDIFLORA L.PERS) LEAVES EXTRACT ADMINISTRATION ON THE DECREASE OF LEUKOCYTE LEVEL IN POST-PARTUM MICE (MUS MUSCULUS) INFECTED WITH STREPTOCOCCUS AGALACTIAE - HEPPY RINA MARDIANA; Surya Mustika Sari; YUFI ARIS LESTARI; ANIK SUPRIANI; NANIK NUR ROSYIDAH; TITIEK IDAYANTI; HERLINA HERLINA (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
Introduction: Maternal Mortality Rate (MMR) is indicator of public health degree. The cause of maternal mortality is postpartum infection. Streptococcus agalactiae bacterium contributes to postpartum infection incidence through vaginal or reproductive organ injury. Infection incidence is characterized with the increased level of leukocyte. The treatment of post-partum infection is done by administering antibiotics. Red sesbania leaves contains active substance that can inhibit the microbial growth. Objective: This research aimed to find out the effect of red sesbania leaves extract administration as antimicrobial agent to decrease leukocyte level in post partum mice (Mus musculus) infected with Streptococcus agalactiae. Method: The method employed was true experimental one with post test control group design, by dividing postpartum mice into 4 groups: one control group and three treatment groups at doses of 125 mg/kgBW, 250 mg/kgBW, and 500 mg/kgBW. All 0-12 hour post partum mice were inoculated with Streptococcus agalactiae bacterium. The administration of 1 ml red sesbania leaves extract in treatment group was conducted 2 hours after the bacterial administration at doses of 125 mg/kgBW, 250 mg/kgBW, and 500 mg/kgBW. Result: The result of analysis shows p < 0.05, indicating that the decrease of leukocyte level in all treatment groups (P1, P2, P3). Conclusion: Red sesbania leaves extract has antimicrobial activity that can reduce leukocyte level, thereby can be used as an alternative therapy to decrease maternal mortality rate due to post-partum infectin. KEYWORDS Red sesbania leaves extract, postpartum mice, leukocyte level, Streptococcus agalactiae.